Analisis Bibliometrik Formulasi Poliherbal sebagai Afrodisiak: Tinjauan Tren Penelitian Terkini - Kartika, I Gusti Agung Ayu; Nugraha, Iwan Saka; Mahardika, Ida Bagus Putra; Suryani, Suryani (Jurnal Ilmiah Medicamento, 2025)
In recent years, the therapeutic potential of polyherbal formulations as aphrodisiacs, particularly as natural alternatives to synthetic treatments for sexual health disorders, has garnered significant attention. Polyherbal formulations are believed to enhance efficacy through synergistic effects, making them a preferred option in both traditional and modern therapeutic practices. This review aims to provide a comprehensive analysis of research trends relating to the use of polyherbal formulations for aphrodisiac purposes. A bibliometric analysis was conducted using the Scopus database, extracting relevant articles with the keywords 'Aphrodisiac AND Polyherbal OR Combination.' From an initial pool of 88 articles, 16 were selected for in-depth analysis. VOSviewer software was used to visualize collaboration networks, co-authorship patterns, and keyword trends, highlighting the increasing research interest in polyherbal formulations for sexual health enhancement. The narrative review supplements these findings by exploring study methodologies, sources of herbal ingredients, formulation compositions, and commonly used herbs. Results indicate that while polyherbal aphrodisiac formulations show promising therapeutic potential, research in this field remains fragmented, with limited clinical trials evaluating safety and efficacy. The most frequently studied herbs include Tribulus terrestris, Mucuna pruriens, and Withania somnifera, known for their effects on testosterone levels, vascular function, and libido enhancement. Future studies should focus on clinical validation, standardization, and pharmacokinetic assessments to facilitate their integration into modern medical practice. These findings provide valuable insights for researchers and industries developing polyherbal-based nutraceutical and pharmaceutical products.